Development of Multi-representation Integrated Learning Media to Understand and Translate the Qur'an in Teaching the Qur'an and Hadith in Elementary Schools - Edhy Rustan; Sela Maria Ningsih; Fauziah Zainuddin (STAI Hubbulwathan Duri, 2022)
Research on the development of media translating the Qur'an was made to determine the need, design, and validity of learning media solving in the learning material of the Qur'an and Hadith in class III MI Dato Sulaiman Palopo. This research method is a research and development (RD) method. The development model used in this development is the ADDIE model (analysis, design, development, implementation, evaluation), but it was only carried out to the development stage in this study. The subject of this research involved 30 students. Data were collected through observation, interviews, and document searches analyzed qualitatively and quantitatively. The needs analysis results show that students need interesting symbols/pictures as learning media and add lesson content well. Learning media is designed by integrating multi-representation in Sempokas media. The feasibility of media teaching materials translating the Qur'an was carried out with the assessment of media experts with a grade level (89.5%), material experts (95.8%), linguists (91.6%), and subject teachers (96, 4%) excellent category. Thus, Sempokas media can be applied in learning to understand and translate Surah Al Ikhlas